Money laundering: The paradox of deterrence mechanism - Adeniyi, Nasir Maruf; Zul Kepli, Mohd Yazid; Mohd Yasin, Norhashimah (Zes Rokman Resources, 2016)
The menace of money laundering is globally acknowledged and the spate of its increase remains unabated. However, a potent tool to deal effectively with this problem lies in the procedure and efficacy of prosecution. Though a lot has been achieved in term of legal and regulatory framework, it is imperative to note that in an environment where corrupt practises remained unpunished due to lack of enforcement, all efforts are likely to be lost. Law enforcement and other supporting agencies will unlikely have any real impact.